Question
upstudy study bank question image url

Rewrite the expressions that follow as the sine or cosine of a single angle and evaluate where possible without a calculator. \( 2.1 \sin 68^{\circ} \cos 22^{\circ}+\cos 68^{\circ} \sin 22^{\circ} \) \( 2.2 \cos 28^{\circ} \cos 2^{\circ}-\sin 28^{\circ} \sin 2^{\circ} \) \( 2.3 \cos 108^{\circ} \cos 188^{\circ}+\sin 252^{\circ} \sin 172^{\circ} \) \( 2.4 \sin 70^{\circ} \cos 10^{\circ}-\cos 80^{\circ} \cos 70^{\circ} \) \( 2.5 \sin 4 x \sin 3 x+\cos 4 x \cos 3 x \) \( 2.6 \quad \sin \left(90^{\circ}-x\right) \cos x+\cos \left(90^{\circ}+x\right) \sin x \)

Ask by Young Carroll. in South Africa
Feb 19,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

1. \(2.1 = 1\) 2. \(2.2 = \frac{\sqrt{3}}{2}\) 3. \(2.3 = \sin(10^{\circ})\) 4. \(2.4 = \frac{\sqrt{3}}{2}\) 5. \(2.5 = \cos(x)\) 6. \(2.6 = \cos(2x)\)

Solution

To rewrite the given expressions as the sine or cosine of a single angle, we can use the angle addition and subtraction formulas. Let's go through each expression step by step. ### Expression 2.1 \[ 2.1 \quad \sin 68^{\circ} \cos 22^{\circ} + \cos 68^{\circ} \sin 22^{\circ} \] This expression can be rewritten using the sine addition formula: \[ \sin(a) \cos(b) + \cos(a) \sin(b) = \sin(a + b) \] Here, \(a = 68^{\circ}\) and \(b = 22^{\circ}\): \[ = \sin(68^{\circ} + 22^{\circ}) = \sin(90^{\circ}) = 1 \] ### Expression 2.2 \[ 2.2 \quad \cos 28^{\circ} \cos 2^{\circ} - \sin 28^{\circ} \sin 2^{\circ} \] This expression can be rewritten using the cosine subtraction formula: \[ \cos(a) \cos(b) - \sin(a) \sin(b) = \cos(a + b) \] Here, \(a = 28^{\circ}\) and \(b = 2^{\circ}\): \[ = \cos(28^{\circ} + 2^{\circ}) = \cos(30^{\circ}) = \frac{\sqrt{3}}{2} \] ### Expression 2.3 \[ 2.3 \quad \cos 108^{\circ} \cos 188^{\circ} + \sin 252^{\circ} \sin 172^{\circ} \] This expression can be rewritten using the cosine addition formula: \[ \cos(a) \cos(b) + \sin(a) \sin(b) = \cos(a - b) \] Here, \(a = 108^{\circ}\) and \(b = 188^{\circ}\): \[ = \cos(108^{\circ} - 188^{\circ}) = \cos(-80^{\circ}) = \cos(80^{\circ}) = \sin(10^{\circ} \] ### Expression 2.4 \[ 2.4 \quad \sin 70^{\circ} \cos 10^{\circ} - \cos 80^{\circ} \cos 70^{\circ} \] We can rewrite \(\cos 80^{\circ}\) as \(\sin 10^{\circ}\): \[ = \sin 70^{\circ} \cos 10^{\circ} - \sin 10^{\circ} \cos 70^{\circ} \] Using the sine subtraction formula: \[ = \sin(70^{\circ} - 10^{\circ}) = \sin(60^{\circ}) = \frac{\sqrt{3}}{2} \] ### Expression 2.5 \[ 2.5 \quad \sin 4x \sin 3x + \cos 4x \cos 3x \] This expression can be rewritten using the cosine addition formula: \[ \sin(a) \sin(b) + \cos(a) \cos(b) = \cos(a - b) \] Here, \(a = 4x\) and \(b = 3x\): \[ = \cos(4x - 3x) = \cos(x) \] ### Expression 2.6 \[ 2.6 \quad \sin(90^{\circ} - x) \cos x + \cos(90^{\circ} + x) \sin x \] Using the identities \(\sin(90^{\circ} - x) = \cos x\) and \(\cos(90^{\circ} + x) = -\sin x\): \[ = \cos x \cos x - \sin x \sin x = \cos^2 x - \sin^2 x = \cos(2x) \] ### Summary of Results 1. \(2.1 = 1\) 2. \(2.2 = \frac{\sqrt{3}}{2}\) 3. \(2.3 = \sin(10^{\circ})\) 4. \(2.4 = \frac{\sqrt{3}}{2}\) 5. \(2.5 = \cos(x)\) 6. \(2.6 = \cos(2x)\)

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

Let's rewrite and evaluate each expression step-by-step. **2.1** Using the sine addition formula \( \sin(a + b) = \sin a \cos b + \cos a \sin b \): \[ 2.1 = \sin(68^{\circ} + 22^{\circ}) = \sin(90^{\circ}) = 1 \] **2.2** Using the cosine subtraction formula \( \cos(a - b) = \cos a \cos b + \sin a \sin b \): \[ 2.2 = \cos(28^{\circ} - 2^{\circ}) = \cos(26^{\circ}) \] **2.3** Using the cosine addition formula \( \cos(a + b) = \cos a \cos b - \sin a \sin b \): \[ 2.3 = \cos(108^{\circ} - 188^{\circ}) = \cos(-80^{\circ}) = \cos(80^{\circ}) \] **2.4** Using the cosine subtraction formula: \[ 2.4 = \sin(70^{\circ}) \cos(10^{\circ}) - \cos(80^{\circ}) \cos(70^{\circ}) = \sin(70^{\circ} - 10^{\circ}) = \sin(60^{\circ}) = \frac{\sqrt{3}}{2} \] **2.5** Using the cosine addition formula: \[ 2.5 = \cos(4x - 3x) = \cos(x) \] **2.6** Using the identity \( \sin(90^{\circ} - x) = \cos x \) and \( \cos(90^{\circ} + x) = -\sin x \): \[ 2.6 = \cos x \cos x - (-\sin x) \sin x = \cos^2 x + \sin^2 x = 1 \] These rewritten expressions give us a concise way of evaluating the trigonometric combinations without a calculator!

Related Questions

8. Simplify without using a calculator. (8.1) \( \frac{\sin \left(180^{\circ}-x\right) \cdot \tan \left(360^{\circ}-x\right)}{\cos \left(80^{\circ}-x\right)} \times \frac{\cos \left(-180^{\circ}-x\right)}{\cos \left(360^{\circ}+x\right) \sin \left(360^{\circ}-x\right)} \) \( 8.2 \frac{\cos 135^{\circ} \sin 160^{\circ}}{\sin 225^{\circ} \cos 70^{\circ}} \) (8.3) \( \frac{\sin (-\theta)+\cos 120^{\circ}+\tan \left(-180^{\circ}-\theta\right)}{\sin ^{2} 225^{\circ}-\tan (-\theta)-\cos \left(90^{\circ}+\theta\right)} \) B.4 \( 4^{x} \frac{\sin 247^{\circ} \cdot \tan 23^{\circ} \cdot \cos 113^{\circ}}{\sin \left(-157^{\circ}\right)} \) (8.5) \( \frac{3 \cos 150^{\circ} \cdot \sin 270^{\circ}}{\tan \left(-45^{\circ}\right) \cdot \cos 600^{\circ}} \) 8.6) \( \frac{\tan \left(180^{\circ}-x\right) \cdot \sin \left(90^{\circ}+x\right)}{\sin (-x)}-\sin y \cdot \cos \left(90^{\circ}-y\right) \) \( 8.7 \frac{\tan 30^{\circ} \cdot \sin 60^{\circ} \cdot \cos 25^{\circ}}{\cos 135^{\circ} \cdot \sin \left(-45^{\circ}\right) \cdot \sin 65^{\circ}} \) 6.8) \( \frac{\tan \left(180^{\circ}-x\right) \cdot \sin \left(90^{\circ}-x\right)}{\cos \left(90^{\circ}+x\right)}-\frac{\cos \left(180^{\circ}-x\right)}{\sin \left(90^{\circ}+x\right)} \) \( 8.9 \frac{\sin 189^{\circ}}{\tan 549^{\circ}}-\frac{\cos ^{2}\left(-9^{\circ}\right)}{\sin 99^{\circ}} \) Solving trigonometric equations (no calculators) (1.) If \( \sin \mathrm{A}=\frac{-3}{5} \) and \( 0^{\circ}<\mathrm{A}<270^{\circ} \) determine the value of: \( 1.1 \cos A \) \( 1.2 \tan A \). (2.) If \( -5 \tan \theta-3=0 \) and \( \sin \theta<0 \), determine: \( 2.1 \sin ^{2} \theta^{\circ} \) \( 2.25 \cos \theta \) \( 2.3 \quad 1-\cos ^{2} \theta \) 3. If \( 13 \cos \theta+12=0 \) and \( 180^{\circ}<\theta<360^{\circ} \), evaluate: \( 3.2 \tan \theta \) \( 3.1 \sin \theta \cos \theta \) \( 3.3 \sin ^{2} \theta+\cos ^{2} \theta \). (4.) If \( 3 \tan \theta-2=0 \) and \( \theta \in\left[90^{\circ} ; 360^{\circ}\right] \), determine, the value of \( \sqrt{13}(\sin \theta-\cos \theta \) (5.) If \( \cos 52^{\circ}=k \) as illustrated in the diagram, determine each of the following i
Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy